WEEKEND EFFECT ON IMPLIED VOLATILITY Empirical Research on Eurex Eqyity Options - Lehtimäki, Jussi (My University, 2008)
This thesis investigates what effects weekend can have for the pricing and valuation of equity options. It is investigated if the weekend effect exists on option market implied volatilities, and if the implied volatility reaction differs between firms from different industry areas. Data used in the study is from the Eurex option market, and consists of the implied volatilities of DaimlerChrysler, Nokia, Siemens, E. ON, Deutsche bank, Lufthansa and Shell. Logarithmic at-the-money implied volatility differences for these seven firms are calculated, and regression framework is adopted in the empirical part to express the results. Dummy variables are used to distinguish the effect of the weekend. Moreover it is tested if different time to maturities should be used between different underlyings in option valuation. The main question is, should the time value of the weekend be included in the options value or not. To test this two portfolios are constructed based on hypothetical weekend risk preferences, so that other portfolio consists of firms that are likely to react to events that happen mostly during the week, and the other portfolio includes firms that are vulnerable to events that can occur just as well during the weekend. Empirical results show that in general weekend effect exists in implied volatilities. This result is in accordance with earlier research. Results from the portfolio regressions however are somewhat different, as portfolio of firms with low risk on weekends does not react to the weekend, and portfolio with firms more sensitive to weekend experience the weekend effect. Results of the study imply that weekend can not be discarded when option pricing is considered, as the weekend effect seems to exist. Results also raise consideration of the unique properties of different firms regarding sensitivity to the weekend, as awareness of this can have implications to the valuation of such an option.
Keywords: options; implied volatility; weekend effect; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|